Rehabilitation in patients with pulmonary arterial hypertension - Keusch, Stephan; Benjamin, Nicola; Grünig, Ekkehard (Swiss medical weekly, 2017)
For many years, PAH patients were advised to avoid strenuous activities. Now, pulmonary rehabilitation is a recommended therapy in addition to optimal medical therapy, if performed within a highly experienced team under expert supervision.